(untitled) (Global Journal of Management and Business Research, 2019)
Corporate governance is an important issue in the regional and international organizations, and interest in this issue has emerged as a series of different financial crises that rocked many companies and triggered by financial corruption, lack of control, experience, skill, lack of transparency, in addition to mismanagement, the loss of money has led many investors to turn to companies that implement the concept of corporate governance .As a result, the concept of corporate governance has become one of the main pillars of economic units, and due to the growing interest in the concept of governance, many organizations have been keen to study this concept and analysis, the most important of these institutions are the International Monetary Fund and the Organization of Economic Cooperation and Development.